Faktor Faktor Psikologis Dan Demografis Yang Mempengaruhi Fear Of Crime Mahasiswa - M Rasyid Ridha; S. Evangeline I. Suaidy (‎‎‎TAZKIYA Journal of Psychology, 2017)
This study aims to determine the effect of variable perception of neighborhood, personality, religiosity ,victimization and gender towards fear of crime on UIN Syarif Hidayatullah Jakarta students.The subject in this research are 289 students wich were taken with non-probability sampling techniques. The researchers modify scales consists of fear of crime scale developed by Gabriel and Greve, Perception of Block Problems, Eysenck Personality Questionnaire-Revised(EPQ-R), religiosity scale developed by Kendler et al and Victimization Index .CFA (Confirmatory Factor Analysis) was used to test the validity of instrument and Multiple Regression Analysis was used as technique to test the research hypothesis. DOI: 10.15408/tazkiya.v22i1.8164